Finite Element Analysis of Cooling Tower Foundation Under Wind Load - Naghshineh, Ali (2006)
The natural draught cooling tower is very important and essential component in the thermal nuclear power stations and industrial power plants. Due to their complexities in geometry the analysis of such type of structures has attracted many researches throughout the world. At the initial stage of this study an attempt was made to write a computer programme for calculating the symmetrical and unsymmetrical wind loading using FORTRAN program, which is compatible with FORTRAN 90 Power Station. The programme was written according to IS: 11504/BS: 4485. The present study deals with physical and material modeling of cooling towerfoundation- soil system. The physical modeling has been carried out using solid twenty-nodded isoparametric element to model the cooling tower, annular raft foundation and soil media. Coupled finite elements were employed to represent the soil media in the near and far field the cooling tower. Cooling tower, foundation-soil system was analyzed under vertical and lateral load generated from wind loads. The soil nonlinearity was taken into the consideration using DUNCAN’S hyperbolic constitutive stress strain law. Therefore, based on those physical and material modeling a finite element program has been written. The computer software package works under FORTRAN power station and the validity of this package has been verified by solving some examples available in the literature. Finally an attempt has been made to demonstrate the applicability of the finite element program in analysis of cooling tower with the total height of 115.35 m and the radius at top, bottom and throat level are 27.535 m, 52.877 m, 25.304 m respectively, subjected to static loading . The response of the structure has been discussed with respect to displacement and stresses. Moreover an attempt has been made to study the effect of the interactive and non-interactive analysis and comparison with conventional analysis was also made. It was concluded that the interactive analysis of the cooling tower-foundation-soil media plays a major role in releasing the stresses in the cooling tower, particular at the bottom ring beam.